Developing a scale for Assessing the Quality of E-learning Service in Saudi Universities: An Applied Study at King Khalid University - Abha - Mohammed Alsagheer Qasem Alshaebi; Yasir Tageldin Abubaker Attico (University of Science and Technology, Yemen, 2019)
The aim of this study was to build a scale for assessing the quality of electronic learning service in Saudi universities, which has been named "E-L-SQUAL". The study was carried out during five stages using the scientific methodology for developing scales. The sample of the study consisted of 729 male and female students of King Khalid University. The data were subjected to statistical analysis using the SPSS program. A number of statistical methods were used for checking the validity, consistency and, reliability, as well as exploratory factor analysis (EFA) to determine the quality of the e-learning service. In addition, the confirmatory factor analysis (CFA) conducted by using AMOS statistical program. Finally, all the study results confirmed the validity of the (E-L-SQUAL) scale, which consisted of (43) items, divided into six dimensions of quality: content, technology, support, user interface, assessments, security and communication. Keywords: scale, evaluation, service quality, e-learning, E-L-SQUAL .